Słowo artystyczne Fiodora Dostojewskiego we współczesnej kulturze (wstęp do analizy adaptacji teatralno-filmowej tekstu literackiego) - Chałacińska, Halina (Studia Rossica Posnaniensia, 2011)
In accordance with theatrical and cinematographic experiments, in the space of model extensive complexity of Dostoyevsky's text, immanent readiness of the verbal material to transform into another type of artistic expression in order to reveal mentally meaningful operations inflicted by the initial impulse of adapted reality can define itself as a distinctive factor of the forming function of the word of the Russian master in the contemporary culture.